Identification of Novel Argonaute Proteins Using a Metagenomic Mining Approach - Ghonaim, Lobna Abdallah (AUC Knowledge Fountain, 2025)
Gene editing is one of the most promising tools in science. It enables precise modifications of an organism's genetic material. Metagenomics is considered a powerful tool that unlocks the broad genetic potential found in uncultured microbial communities. Exploring the genetic diversity of uncultured microbial communities helps identify novel functional proteins with unique properties and make the best use of these diverse microbial ecosystems. We developed and employed a metagenomic-based approach to mine more than 1000 metagenomes for prokaryotic argonaute proteins (pAgos), a potential gene editing machinery encoded in bacterial and archaeal genomes. Our workflow involved strict quality control, sequence assembly, taxonomic classification, profiling and analysis, and annotation. We then identified the presence of key domains such as PIWI and MID. Our methodology ensured effective screening and identification of these proteins across metagenomes from 25 different ecosystems. We analyzed 1,011 publicly available metagenomic datasets from which we identified 905 putative pAgos across these diverse environments by building a custom Hidden Markov Model (HMM) profile. Our analysis identified proteins with substantial diversity and considerable abundance in diverse microbial environments and included novel variants with unique functional characteristics. Our work highlights the power of metagenomics to discover novel functional proteins and presents promising applications for gene editing.